Reduced T and NK Cell Activity in Glioblastoma Patients Correlates with TIM-3 and BAT3 Dysregulation - Farah Ahmady; Peter Curpen; Louis Perriman; Adilson Fonseca Teixeira; Siqi Wu; Hong-Jian Zhu; Arpita Poddar; Aparna Jayachandran; George Kannourakis; Rodney B. Luwor (Cells)
Inhibitory receptors are critical for regulating immune cell function. In cancer, these receptors are often over-expressed on the cell surface of T and NK cells, leading to reduced anti-tumor activity. Here, through the analysis of 11 commonly studied checkpoint and inhibitory receptors, we discern that only HAVCR2 (TIM3) and ENTPD1 (CD39) display significantly greater gene expression in glioblastoma compared to normal brain and lower grade glioma. Cell surface TIM-3, but not ENTPD1, was also elevated on activated CD4+ and CD8+ T cells, as well as on NK cells from glioblastoma patients compared to healthy donor T and NK cells. A subsequent analysis of molecules known to co-ordinate TIM-3 function and regulation was performed, which revealed that BAT3 expression was significantly reduced in CD4+ and CD8+ T cells, as well as NK cells from glioblastoma patients compared to counterparts from healthy donors. These pro-inhibitory changes are also correlated with reduced levels of the activation marker CD69 and the pro-inflammatory cytokine IFNγ in CD4+ and CD8+ T cells, as well as NK cells from glioblastoma patients. Collectively, these data reveal that glioblastoma-mediated CD4+ and CD8+ T cell and NK cell suppression is due, at least in part, to dysregulated TIM-3 and BAT3 expression and the associated downstream immunoregulatory and dysfunctional effects.